Illegal Mining Business in Pidie Aceh Regency (Analysis of Decision Number: 58/PID. B/LH/2022/PN. SGI) - Sayyid Muhammad Charafi; Yasmirah Mandasari Saragih (Yayasan Multidimensi Kreatif, 2024)
Indonesia, an archipelagic country with over 17,000 islands and vast natural resources, faces significant challenges in managing its mining sector. The expansive geographical area and abundant natural wealth present both opportunities and risks. While mining activities contribute to national income and economic growth, they also pose serious environmental and regulatory issues. Illegal mining, in particular, exacerbates these problems, leading to environmental degradation and loss of state revenue. Despite the implementation of stringent regulations, illegal mining persists, undermining legal mining operations and environmental sustainability. The case study of illegal mining in Pidie Regency, Aceh, highlights the challenges faced by local authorities in enforcing mining laws. The case of Satria bin Wagiran and Rizki Wahyudi, charged with illegal gold mining, underscores the enforcement difficulties and legal repercussions associated with unauthorized mining activities. This research explores the legal framework governing mining in Indonesia, the impact of illegal mining, and the effectiveness of current enforcement mechanisms. The analysis of Decision Number: 58/Pid.B/LH/2022/PN. SGI provides insights into the legal consequences for illegal mining and the need for improved regulatory measures to safeguard natural resources.